Development of an AI-powered shareable bike rebalancing system - Tu, Anqi (Nanyang Technological University, 2020)
Bike sharing systems with docking stations are widely deployed in many major cities, bringing convenience to citizens and promoting eco-friendly lifestyles. However, they are facing a common problem - the congestion or deficiency of bikes in docking stations due to fluctuation in bike usage. Inefciency in re-distributing bikes among docking stations is challenging for system operators. One approach to address such inefficiency is to rebalance bikes among docking stations with trucks. To allow researchers to study the efficiency of different rebalancing strategies under different conditions, this project aims to develop a simulation testbed.